EFEKTIVITAS PELAKSANAAN PROGRAM PEMBANGUNAN PEDESAAN DI DESA KAUNERAN 1 KECAMATAN SONDER - OLBATA, APRILIA; RURU, JOORIE MARHAEN; PALAR, NOVIE ANDERS (JURNAL ADMINISTRASI PUBLIK, 2018)
The implementation of the Rural Development Program is one form of the government indeveloping villages. With rural development, it is expected that a change will occur in various aspects,including efforts to improve the welfare of the community through the pace of economic growth. Thepurpose of this study is to determine the level of effectiveness and the factors that influence it. To measurethe level of effectiveness, researchers use three measures of effectiveness according to Ducan, who isquoted by Richard M. Steers in his book "Organizational Effectiveness" (2005), namely the level ofachievement of objectives, integration, and adaptation to the Effectiveness of the Implementation of RuralDevelopment Programs in Kauneran 1 Village, Sonder District. Researchers strive to be able to observeand analyze the development progress that has been planned. Among them by observing based on theresults of interviews of 15 informants who are the village government, community figures, religiousleaders, and the surrounding community. Based on the results of the study, it can be seen that with thedevelopment of the right target, it has increased the pace of the economy in the local community.Keywords : Effectiveness, Rural Development.